Lower Cretaceous rudist biostratigraphy of southem France-a reference for Mesogean correlations - Jean Pierre Masse (Revista Mexicana de Ciencias Geológicas)
The lower Cretaceous rudist fauna of southern France consists of 61 species corresponding to 23 genera belonging to Diceratidae, Requieniidae, Monopleuridae, Caprinidae, Polyconotidae and Radiolitidae… in order to continue, download the full paper in PDF.